(untitled) (Research, Society and Development, 2025)
Introduction: Entrepreneurship in obstetric nursing has expanded professional autonomy and diversified the forms of care throughout pregnancy, childbirth and the postpartum period, especially through the development of nursing offices, clinics and home-based services. These practices enable safer, more humanized and patient-centered care focused on the needs of women and newborns. Objective: To analyze, through an integrative literature review, the relationship between entrepreneurship in obstetric nursing and the safety of childbirth and postpartum care. Methodology: Studies published between 2018 and 2025 were identified in the SciELO, LILACS and PubMed/MEDLINE databases, complemented by manual searches in national journals. Results: Of the 45 studies initially found, 15 met the methodological criteria and composed the final sample. The evidence indicates that entrepreneurial practices strengthen birth planning, increase access to humanized care, improve clinical follow-up and promote continuity of assistance. Conclusion: Entrepreneurship in obstetric nursing contributes to safer and higher-quality care models by integrating professional autonomy, technical-scientific knowledge and practices centered on the needs of women and newborns.